0.7x-0.6(5-2x)=-0.9(x-6)

Simple and best practice solution for 0.7x-0.6(5-2x)=-0.9(x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.7x-0.6(5-2x)=-0.9(x-6) equation:


Simplifying
0.7x + -0.6(5 + -2x) = -0.9(x + -6)
0.7x + (5 * -0.6 + -2x * -0.6) = -0.9(x + -6)
0.7x + (-3 + 1.2x) = -0.9(x + -6)

Reorder the terms:
-3 + 0.7x + 1.2x = -0.9(x + -6)

Combine like terms: 0.7x + 1.2x = 1.9x
-3 + 1.9x = -0.9(x + -6)

Reorder the terms:
-3 + 1.9x = -0.9(-6 + x)
-3 + 1.9x = (-6 * -0.9 + x * -0.9)
-3 + 1.9x = (5.4 + -0.9x)

Solving
-3 + 1.9x = 5.4 + -0.9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '0.9x' to each side of the equation.
-3 + 1.9x + 0.9x = 5.4 + -0.9x + 0.9x

Combine like terms: 1.9x + 0.9x = 2.8x
-3 + 2.8x = 5.4 + -0.9x + 0.9x

Combine like terms: -0.9x + 0.9x = 0.0
-3 + 2.8x = 5.4 + 0.0
-3 + 2.8x = 5.4

Add '3' to each side of the equation.
-3 + 3 + 2.8x = 5.4 + 3

Combine like terms: -3 + 3 = 0
0 + 2.8x = 5.4 + 3
2.8x = 5.4 + 3

Combine like terms: 5.4 + 3 = 8.4
2.8x = 8.4

Divide each side by '2.8'.
x = 3

Simplifying
x = 3

See similar equations:

| 6x+8+3(m+2)=12.6 | | -6(y-2y)+2=-6(3y-y)+9+17y | | 7p+12=13+5p | | VAR(4-3Z)=0 | | x^5-x^4-2x^3+2x^2+24=0 | | Y=.50x-100 | | 4z-a=3 | | y=x^9/x^13 | | 12/5(r-2)=2/3(3r-2(2r-1)) | | y=(7x-1)(x+3) | | y=(7x+1)(x-3) | | -3(y-4)=-5(y+2) | | x=(7x+1)(x-3) | | 5*4/8*-1/-7= | | 8y+6=-y-2 | | 11/1331 | | X=(y+6)(y+8) | | 75x^3+65x^2+10x=0 | | 5x+1y+0.05z=100 | | 31/2=62/t | | n/0.28=0.3/0.42 | | 18t=27(t-8) | | 16/19=p/13 | | (30/250)*5 | | 18t=17(t-8) | | 14/20=p/16 | | 8b^4(4b^3-7)= | | 14/8=28/m | | 5(x-6)=2/x | | z+5=z-7 | | 99/100*(0.4) | | 99/100*(0.4=) |

Equations solver categories